DESIGN AND MOLECULAR DOCKING STUDY ADME/TOX COMPOSITION COMPOUND OF EUCALYPTUS ESSENTIAL OIL (Eucalyptus Camaldulensis DEHNH.) AS AN INHIBITOR OF α-AMYLASE AND α-GLUCOSIDASE ENZYMES - Listyani, Tiara Ajeng; Artini, Kusumaningtyas Siwi; Sejati, Siti Laila Utari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2025)
Background: Composition compound of Eucalyptus Essential Oil (Eucalyptus Camaldulensis DEHNH.) have been reported as inhibitors of α-amylase and α-glucosidase in vitro for antidiabetics. Objective: This study aims to determine the interaction patterns and ΔGbind between Composition compound of Eucalyptus Essential Oil on α-amylase and α-glucosidase with prediction ADME and toxicity. Method: Composition compound of Eucalyptus Essential Oil was optimized for geometry using VegaZZ and prepared as a ligand. Next, preparations for target receptors, α-amylase and α-glucosidase. Validation of docking method and molecular docking analysis using PyRx-Python-AutoDock Vina. Prediction of ADME values used SwissADME, while Toxicity Prediction used Toxtree. Results: There are hydrogen bond interactions between the amino acids GluA:233 and AspA:300, and AspA:197 in the compound 5-Amino-4-cyano-3-(4-ethyllaminobutyl) pyrazole from the α-amylase and AsnA:797 and AsnA:496 from the α-glucosidase. There is no relationship between ΔGbind and the Composition compound of Eucalyptus Essential Oil with the enzyme binding site. The compound 5-Amino-4-cyano-3-(4-ethyllaminobutyl) pyrazole has the lowest ΔGbind value and the RMSD on α-amylase and α-glucosidase is -3.7 kcal/mol; 1.85Å, -4.1 kcal/mol; 1.565Å. The results of the ADME test were found meet the Lipinski Five Rule. The toxicity test results are not carcinogenic or mutagenic, except 5-Amino-4-cyan0-3-(4-ethyllaminobutyl) pyrazole. The new compound design of 3-(4-(ethylamino)butyl)-5-hydroxy-1H-pyrazole-4-carbonitrile showed a decrease in ΔGbind of α-amylase with fixed ADME profile and safer toxicity parameters. Conclusion: Composition compound of Eucalyptus Essential Oil (Eucalyptus Camaldulensis DEHNH.) has the potential to be an oral medicine candidate inhibitors of α-amylase and α-glucosidase for antidiabetes.